Efficacy and safety of three second-line antiretroviral regimens in HIV-infected patients in Africa. (31st July 2015) - Ciaffi, Laura; Koulla-Shiro, Sinata; Sawadogo, Adrien; le Moing, Vincent; Eymard-Duvernay, Sabrina; Izard, Susanne; Kouanfack, Charles; Ngom Gueye, Ndeye Fatou; Fobang, Avelin Aghokeng; Reynes, Jacques; Calmy, Alexandra; Delaporte, Eric
<x xml:space="preserve">Abstract</x> Objective: WHO recommends ritonavir-boosted protease inhibitor with two nucleoside reverse transcriptase inhibitors in HIV-infected patients failing non-nucleoside reverse transcriptase inhibitor-based first-line treatment. Here, we aimed to provide more evidence for the choice of nucleoside reverse transcriptase inhibitor and boosted protease inhibitor. Design: ANRS 12169 is a 48-week, randomized, open-label, non-inferiority trial in three African cities, comparing efficacy and safety of three second-line regimens. Methods: Patients failing non-nucleoside reverse transcriptase inhibitor-based antiretroviral therapy with confirmed plasma HIV-1 viral load above 1000 copies/ml were randomly assigned to tenofovir/emtricitabine + lopinavir/ritonavir (control group as per WHO recommendations), abacavir + didanosine + lopinavir/ritonavir (ABC/ddI group) or tenofovir/emtricitabine + darunavir/ritonavir (DRV group) regimens. The primary endpoint was the proportion of patients with plasma vral load below 50 copies/ml at week 48 in the modified intention-to-treat population. Non-inferiority was pre-specified with a 15% margin. Results: Of the 454 randomized patients, 451 were included in the analysis. Globally, 294 (65.2%) and 375 (83.2%) patients had viral load below 50 and 200 copies/ml, respectively, at week 48. The primary endpoint was achieved in 105 (69.1%) control group patients versus 92 (63.4%) in the ABC/ddI (difference 5.6%, 95% confidence interval –5.1 to 16.4) and 97 (63.0%) in the DRV (difference 6.1%, 95% confidence interval –4.5 to 16.7) groups (non-inferiority not shown). Overall, less number of patients with baseline viral load at least 100 000 copies/ml (n = 122) had a viral load below 50 copies/ml at week 48 (37.7 versus 75.4%; P < 0.001). Conclusions: The three second-line regimens obtained similar and satisfactory virologic control and confirmed the WHO recommendation (TDF/FTC/LPVr) as a valid option. However, the suboptimal response for patients with high viral load warrants research for improved strategies.